2016
DOI: 10.1117/1.jbo.21.12.126021
|View full text |Cite
|
Sign up to set email alerts
|

Direct comparison between confocal and multiphoton microscopy for rapid histopathological evaluation of unfixed human breast tissue

Abstract: , "Direct comparison between confocal and multiphoton microscopy for rapid histopathological evaluation of unfixed human breast tissue," J. Abstract. Rapid histopathological examination of surgical specimen margins using fluorescence microscopy during breast conservation therapy has the potential to reduce the rate of positive margins on postoperative histopathology and the need for repeat surgeries. To assess the suitability of imaging modalities, we perform a direct comparison between confocal fluorescence m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…This shows the correlation between the false-color images created using nonlinear microscopy and H&E images. 106 The study concluded that confocal florescence microscopy offered similar information to nonlinear microscopy, but at much lower cost. When magnification was increased significantly, a blurring effect did occur with confocal fluorescence microscopy (CFM); however, nonlinear microscopy offers molecular information with very strong sensitivity and specificity.…”
Section: Nonlinear Microscopymentioning
confidence: 97%
“…This shows the correlation between the false-color images created using nonlinear microscopy and H&E images. 106 The study concluded that confocal florescence microscopy offered similar information to nonlinear microscopy, but at much lower cost. When magnification was increased significantly, a blurring effect did occur with confocal fluorescence microscopy (CFM); however, nonlinear microscopy offers molecular information with very strong sensitivity and specificity.…”
Section: Nonlinear Microscopymentioning
confidence: 97%
“…However, the ability to image through surgical debris, blood and tissue marking ink is an important advantage of NLM that enables imaging of tissue aspects that have surface contamination typical of breast surgical specimens. In a previous manuscript, we evaluated CFM and found its ability to image subsurface features to be significantly more limited than NLM [28], while MUSE can only image a single plane on the tissue surface and so cannot perform subsurface assessment [32]. OCT provides excellent subsurface imaging but has limited nuclear contrast.…”
Section: Discussionmentioning
confidence: 99%
“…Because physical sectioning accounts for the vast majority of processing delay for both FFPE and FSA histology, optical sectioning can dramatically reduce processing times and enable intraoperative histological examination in scenarios where FFPE and FSA histology are too time consuming. Various methods have been proposed for imaging breast, prostate and other surgical margins without physical sectioning, including optical coherence tomography (OCT) [18][19][20][21][22], reflectance confocal microscopy (RCM) [23,24], confocal fluorescence microscopy (CFM) [25][26][27][28][29], structured illumination microscopy (SIM) [30], light sheet microscopy [31], microscopy with ultraviolet surface excitation (MUSE) [32,33], and nonlinear microscopy (NLM) [34][35][36][37][38]. Stimulated Raman scattering (SRS) has also been demonstrated for surgical histology [39], but typically has appreciably lower imaging speed or signal to noise ratio when performed without physical sectioning in reflectance mode.…”
Section: Introductionmentioning
confidence: 99%
“…This is an attractive strategy that can seamlessly integrate the technical advantages of multiple techniques while minimizing the practical limitations of each. Giacomelli et al 20 and Yoshitake et al 21 demonstrated the use of confocal and multiphoton microscopy for virtual H&E imaging of excised sliced breast specimens, enabling determination of various breast pathologies. Glaser et al 22 recently demonstrated volumetric imaging of fresh slices of breast and prostate tissue immersed in silicone oil using light sheet microscopy.…”
Section: Breast Cancer Surgery: a Surgicalmentioning
confidence: 99%
“…21,41,42 Journal of Biomedical Optics 021104-5 February 2018 • Vol. 23 (2) Recently, Tu et al 43 and Tu and Boppart 44 developed a platform system based on a pumped photonic crystal fiber source that produced widely coherent supercontinuum suitable for pulse compression and shaping to efficiently drive label-free nonlinear processes of two-and three-photon autofluorescence, secondand third-harmonic generation, and broadband hyperspectral coherent anti-Stokes Raman scattering.…”
Section: Hyperspectral Imaging For Intraoperative Margin Assessment: mentioning
confidence: 99%